ANALISIS TINGKAT PENDAPATAN FBI PADA BANK UMUM YANG TERDAFTAR DI BEI (PERIODE 2015-2017) - Yusniarti Ali; Mohammad Faisal Abdullah; Zainal Arifin (Program Studi Ekonomi Pembangunan, 2019)
The purpose of this research is to analyze the influence of Equity, Assets, and Third Party Funds on fee-based income at commercial banks listed on the Indonesia Stock Exchange for the period 2015-2017, this type of research uses quantitative research, which uses annual financial report data on each bank that was published by the Indonesia Stock Exchange was then analyzed using panel data regression analysis that was processed using Eviews 9. The Result of the first regression show that equity does not have a significant effect on fee-based income with a coefficient of -0.003915 in the second regression result which shows that assets have a significant effect on fee-based income with a coefficient of 0.003511 and in the third regression result show significant effect on fee-based income with a coefficient of 0.001021.